PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PANTUN SISWA SEKOLAH DASAR - Viona Lorenza; Lusi Marleni; Yanti Yandri Kusuma; Mufarizuddin; Fadhilaturrahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low reading skills of students in learning Indonesian language in grade V of SDN 043 Batu Gajah. One solution to overcome this problem is to use the Jigsaw Learning Model. The purpose of this study was to improve students' reading skills in learning Indonesian language material on pantun. The research method used was Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of two meetings and four stages: planning, implementation, observation, and reflection. The research was conducted in May-June 2025. The research subjects were 16 fifth-grade students, comprising 9 males and 7 females. Data collection techniques included documentation, observation, and testing. The results of this study can be summarized as follows: students' pantun reading skills on the Pantun material for Grade V at SDN 043 Batu Gajah were 25% before the intervention, then increased to 37.5% in Cycle I Session I, and further increased to 56.25% in Cycle I Session II. Furthermore, in Cycle II Meeting I, it increased to 68.75%, and in Cycle II Meeting II, it increased to 87.5%. Thus, it can be concluded that using the Jigsaw Learning Model can improve students' pantun reading skills in Indonesian language learning on the pantun material for Grade V at SDN 043 Batu Gajah. Keywords: Pantun Reading Skills, Jigsaw, Indonesian Language